Relationship Between Green Finance Availability and Purchase Intentions in Generation Z and Millennials: Moderating Role of Consciousness - Prasad kdv; Chitta Shyamsunder Shyamsunder; Hariprasad Soni (Qubahan Academic Journal)
This study examines how the availability of green finance influences the purchasing intentions of Generation Z and Millennials, with consciousness as a moderating factor. A structured questionnaire was deployed to collect the data to measure five reflective constructs: purchase intention, Gen Z and Millennials’ green finance, environmental consciousness, future consciousness and status consciousness. The valid responses of 500 participants working at various levels in the information technology industry were subjected to normality tests, factor analysis, and structural equation modeling analysis. The data were normally distributed (Shapiro‒Wilk statistic p>0.05), and the survey instrument maintained internal consistency and reliability, as revealed by the Cronbach’s alpha values (>0.70). The structural equation modeling results revealed an excellent model fit, and the Gen Z and Millennials’ financial availability, future consciousness and status consciousness constructs were statistically significant and impacted the purchasing intentions of Gen Z and Millennials. Slope analysis reveals that consciousness is statistically significant and moderates the relationship between Gen Z and Millennial financing availability and purchase intentions. Consciousness strengthens the positive relationship between Gen Z and millennial finance availability and purchase intentions. The article reports novel findings that affect the purchase intentions of customers regarding the availability of green financing to Generation Z and Millennials. This is a new empirical study in which Generation Z and Millennials. This empirical study highlighted the environmental, social and managerial implications for green finance providers. Green finance opportunities need to be provided to Gen Z and Millennials so that they can make a habit of engaging in green finance practices. This will promote environmental protection, increase greener consumption options, and ensure social equity and sustainable economic development. If the green financing opportunities promoted to Gen Z and Millennials, more businesses can opt for greener options, greener products and greener marketing.